Índice de controle de capitais: uma análise da legislação e seu impacto sobre o fluxo de capital no Brasil no período 1990-2000 - Terra, Maria Cristina; Soihet, Elena (Estudos Econômicos (São Paulo), 2006)
Cardoso and Goldfajn (1997) build an index of capital control for Brazil for the period 1988 to 1995, and they study the impact of the index on the capital flows. This paper computes the same index for the period 1990-2000 and analyzes, quantitavely, the impact of this index on capital flows. The period studied was characterized by the liberalization of capital flows, with a few sub-periods where restriction were imposed, specially to capital outflows. The empirical results show that the capital control index helps explaining the total capital flows between 1990 and 2000, together with deviation from covered interest parity, the Real Stabilization Plan, and the impact of the Mexican, Asian and Russian crises.